PENGENALAN SIFAT ASAM BASA BAHAN MAKANAN DENGAN MENGGUNAKAN pH INDIKATOR DAN KERTAS LAKMUS DI YAYASAN LAYAR DAKWAH - Masdania Zurairah Siregar; Muhammad Adam; Abdul Azis; Zaharuddin (Jurnal Cakrawala Ilmiah, 2022)
This service is carried out at the Layar Da'wah Foundation, where one of its activities is about vocational. So it is very important to know the acidic nature of some food ingredients consumed by the body. The materials to be used using red and blue litmus paper and also the use of pH indicators are carbohydrate-based foodstuffs such as cassava and protein-based ingredients such as eggs, as well as fruits such as oranges. With red and blue litmus paper, you can tell whether the food is acidic or alkaline by placing it on the litmus paper, if the litmus paper is red, it means that the food is acidic, and if the litmus paper is blue, it is alkaline. The pH indicator functions to determine the limits of how acidic and alkaline the food is. Where the limit of the pH indicator between smaller 7 means the food is acidic and greater than seven then the food is alkaline.